Republic of Congo : Joint Staff Advisory Note of the Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2005)
This Joint Staff Advisory Note examines Congo's Interim Poverty Reduction Strategy Paper (I-PRSP). The I-PRSP recognizes the lack of recent and good quality data on poverty, and recommends new surveys and studies to improve poverty assessment and analysis. On the basis of the sparsely available data, the I-PRSP estimates that at least 50 percent of the population is poor. The I-PRSP also links the high poverty incidence to a significant decline in per capita output and the deterioration of basic social services.